2008
DOI: 10.1111/j.1600-079x.2008.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimized synthesis of the melatonin metabolite N1‐acetyl‐N2‐formyl‐5‐methoxykynuramine (AFMK)

Abstract: N(1)-acetyl-N(2)-formyl-5-methoxykynuramine (AFMK) is the product of oxidative pyrrole ring cleavage of melatonin. AFMK and its deformylated derivative N(1)-acetyl-5-methoxykynuramine (AMK) are compounds for which there are increasing demands because of their antioxidant, immunomodulatory and anti-inflammatory properties. Here, we sought to determine the best reaction conditions for preparation of AFMK using chlorpromazine (CPZ) as a co-catalyst in the peroxidase-mediated oxidation of melatonin. The parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[43] suggested that AFMK is formed from 2‐hydroxymelatonin, which is consistent with our results because this compound was the primary product formed using either Tau‐NHCl or Tau‐NHBr as the oxidant. Another pathway for production of AFMK involves the formation of transient melatonin radicals and subsequent interaction with molecular oxygen [35]. In our results, this pathway was eliminated as a possibility because the yield of AFMK was not increased by bubbling oxygen or decreased by purging the reaction medium with nitrogen.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…[43] suggested that AFMK is formed from 2‐hydroxymelatonin, which is consistent with our results because this compound was the primary product formed using either Tau‐NHCl or Tau‐NHBr as the oxidant. Another pathway for production of AFMK involves the formation of transient melatonin radicals and subsequent interaction with molecular oxygen [35]. In our results, this pathway was eliminated as a possibility because the yield of AFMK was not increased by bubbling oxygen or decreased by purging the reaction medium with nitrogen.…”
Section: Discussionmentioning
confidence: 72%
“…The experiments described earlier were performed taking into account the well‐known effects of pH on the efficiency of melatonin oxidation and the profile of the products produced from melatonin [34, 35]. Another reason for performing these experiments was the fact that in aqueous solution Tau‐NHCl exists in equilibrium with its dichlorinated form, taurine dichloramine (Tau‐NCl 2 ) [36].…”
Section: Resultsmentioning
confidence: 99%
“…In brief, the following categories of agents were shown to generate this kynuramine; enzymatic: myeloperoxidase + O 2 • − [31–35] (for involvement of O 2 • − instead of hydrogen peroxide see ref. [34]); hemoperoxidase (horseradish) compound III + O 2 • − [31, 36] (AFMK formation by both myeloperoxidase and horseradish peroxidase can be enhanced by chlorpromazine [37, 38]); pseudoenzymatic: oxoferryl hemoglobin [39, 40]; cytochrome c + hydrogen peroxide (H 2 O 2 ) [41]; hemin + H 2 O 2 or O 2 • − [9, 22–24]; nonradical photocatalytic: singlet oxygen [O 2 ( 1 Δ g )] [23, 42–44]; O 2 + UV [45–47] (details of direct photochemical melatonin destruction by UV light [48]); combinations of radicals (including photocatalysis): protoporphyrinyl IX cation radicals + O 2 •− [23, 42, 43, 49, 50]; substituted anthranilyl radicals + O 2 • − [27, 51, 52]; NAD radical (NAD • ) + O 2 • − [53]; hydroxyl radicals ( • OH) + O 2 • − [23, 24, 54]; carbonate radicals (CO 3 • − ) + O 2 • − [25, 27, 52, 55–57].…”
Section: The Kynuric Pathway: Multiple Reactions and The Question Of mentioning
confidence: 99%
“…Melatonin is also a potent endogenous free-radical scavenger and antioxidant [412]. Melatonin interacts with a variety of reactive oxygen and nitrogen species, including hydroxyl radical [13], singlet oxygen [14], nitric oxide [13], hydrogen peroxide [15], peroxynitrite anion [7], hypocholorous acid [16], and the superoxide anion [17]. The antioxidant properties of melatonin are considerably different from classical antioxidants such as vitamin C and vitamin E. These classic antioxidants are usually electron donors and undergo redox cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is also a potent endogenous free-radical scavenger and antioxidant [4][5][6][7][8][9][10][11][12]. Melatonin interacts with a variety of reactive oxygen and nitrogen species, including hydroxyl radical [13], singlet oxygen [14], nitric oxide [13], hydrogen peroxide [15], peroxynitrite anion [7], hypocholorous acid [16], and the superoxide anion [17]. The antioxidant properties of melatonin are considerably different from classical antioxidants Abstract: The interactions of melatonin, a potent endogenous antioxidant, with reactive oxygen species generate several products that include N 1 -acetyl-N 2 -formyl-5-methoxykynuramine (AFMK) and N 1 -acetyl-5-methoxykynuramine (AMK).…”
Section: Introductionmentioning
confidence: 99%